Bandwidth Enhancement of 2x1 Microstrip Array Antena Using Slit Technique for Wireless Communication System - Erby Virta Joseph Paays; Syah Alam; Indra Sujati (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2023)
This study proposes a microstrip array antenna with frequency at of 2.3 GHz – 2.5 GHz for various applications, with smaller antena dimensions. The microstrip antenna designed in this study uses a rectangular patch consisting of two patch elements arranged in a linear array. The type of substrate used is FR-4 with a dielectric constant (εr) = 4.3 and a substrate thickness (h) = 1.6 mm. The feeding technique used is indirect feeding using a microstrip line feed. To increase the bandwidth, the antennas are arranged in an array with 50 ohm and 100 ohm microstrip lines. The simulated antenna parameters are return loss value -10 dB, VSWR 2, and gain value. The simulation results of the two-element array design with a substrate size of 123 mm x 65 mm obtained a return loss value of -27.99 dB at a frequency of 2300 MHz, -15.16 dB at a frequency of 2400 MHz, and -29.29 dB. The bandwidth generated in this study is 460 MHz or an increase of up to 283.3% when compared to a 2x1 antenna array without slit. Furthermore, the addition of slits succeeded in reducing the dimensions of 34.43% compared to 2x1 antenna arrays without slits. This antenna is very useful as a wireless communication receiving antena.